2012
DOI: 10.5966/sctm.2012-0054
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Rescue of the Vascular Phenotype of Williams-Beuren Syndrome in Patient Induced Pluripotent Stem Cells

Abstract: Elastin haploinsufficiency in Williams-Beuren syndrome (WBS) leads to increased vascular smooth muscle cell (SMC) proliferation and stenoses. Our objective was to generate a human induced pluripotent stem (hiPS) cell model for in vitro assessment of the WBS phenotype and to test the ability of candidate agents to rescue the phenotype. hiPS cells were reprogrammed from skin fibroblasts of a WBS patient with aortic and pulmonary stenosis and healthy control BJ fibroblasts using four-factor retrovirus reprogrammi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 63 publications
1
64
0
Order By: Relevance
“…Indeed, the hiPS cell-derived vascular precursor cells have been shown to be excellent models to study disease. For example, hiPS cell-derived vascular precursors have been used to derive blood-brain barrier type endothelial cells (ECs) in culture (14) or to study patientspecific EC and smooth muscle cell defects in a Hutchinson Gilford progeria model (15) and rescue the vascular phenotype of Williams-Beuren syndrome (16).…”
mentioning
confidence: 99%
“…Indeed, the hiPS cell-derived vascular precursor cells have been shown to be excellent models to study disease. For example, hiPS cell-derived vascular precursors have been used to derive blood-brain barrier type endothelial cells (ECs) in culture (14) or to study patientspecific EC and smooth muscle cell defects in a Hutchinson Gilford progeria model (15) and rescue the vascular phenotype of Williams-Beuren syndrome (16).…”
mentioning
confidence: 99%
“…SVAS is caused by deletion in the elastin gene (ELN) and is characterized by hyperproliferation of SMCs and narrowing of the ascending aorta (Ge et al, 2012, Kinnear et al, 2013). A mouse model of SVAS was established by deleting the Eln gene in vivo, and primary Eln -null SMCs recapitulate human disease phenotypes (Li et al, 1998).…”
Section: New Therapeutic Approaches Toward Matrix-related Diseasesmentioning
confidence: 99%
“…115 These pathological features were rescued by elastin recombinant protein, thus confirming elastin haploinsufficiency as the cause. Subsequently, hiPSC-SMCs derived from patients with WBS were found to have the same pathological features that were later confirmed by Kinnear et al 116 The use of hiPSC platform was a significant breakthrough, as hemizygous transgenic mouse models of WBS failed to exhibit supravalvular aortic stenosis. 117 Importantly, the authors found the drug rapamycin, an antiproliferative agent, to be effective at reversing the pathological phenotypes, demonstrating the potential use of this FDA-approved drug for the prevention of arterial stenosis following surgical correction.…”
Section: Disease Modeling Using Patient-specific Hipsc Derivativesmentioning
confidence: 66%